ICT for Development : Contributing to the Millennium Development Goals - Lessons Learned from Seventeen infoDev Projects - Batchelor, Simon; Evangelista, Soc; Hearn, Simon; Peirce, Malcolm; Sugden, Susan; Webb, Mike (Washington, DC: World Bank, 2013)
The aim of this paper is to create a publicly available resource that provides concise descriptions of selected infoDev ICT-for-development projects, and their impact on poverty. The paper first presents case studies of a cross-section of projects funded by the infoDev Core Program, followed by an in-depth analysis of the impact, and limits of those projects. The main criterion for selecting projects for case study analysis was to be as representative as possible of the various environments (political, economic, social, geographic) in which infoDev has been operating since its inception. An attempt was also made to provide a balanced sample relative to the success rate of the projects. Rather than selecting the "best projects," the authors, in consultation with the task managers of the projects, gave priority to those initiatives likely to offer the best lessons and knowledge about how to use ICT for development purposes. infoDev case studies show that the presence of a project champion enhances the success of a project (FOOD, Manobi, Voxiva, Fantsuam). The cases also demonstrate that technical and organization capacity can be built over the life of a project.